Canadian service providers' perspectives on reproductive coercion and abuse: a participatory action research to address their needs and support their actions - Lévesque, Sylvie; Rousseau, Catherine; Raynault-Rioux, Laurence; Laforest, Julie (Université d'Ottawa | University of Ottawa, 2023)
Abstract Reproductive coercion and abuse (RCA) is a form of violence that affects sexual and reproductive health. Women and individuals who experienced RCA in an intimate relationship frequently consult service providers (SPs), such as health professionals or violence counselors. The objective of this article, which is the result of a participative action research project targeting RCA perpetrated by in an intimate partner, is twofold: (1) to better understand the practices as well as the barriers and facilitators encountered by SPs and (2) to develop information and awareness tools with them that meet their needs. To this end, we first held focus groups with 31 SPs. The use of thematic analysis revealed intervention strategies that focus on caring and listening, identifying signs of RCA, and creating a safe environment for disclosure. Their practices also focused on harm-reduction strategies and effective referrals. Despite the importance they gave to this issue, lack of time, inappropriate settings, and inadequate training hindered them from intervening effectively with individuals who were victims of RCA. They also indicated the need for easy-to-follow practice guidelines and patient education tools. Based on these findings and the best practices identified in the grey and scientific literature, we developed a practice guide for SPs and a booklet on RCA. The development of these guide and booklets involved a lot of back and forth to meet the needs expressed by the community and health professionals.